2021
DOI: 10.1111/bjd.19885
|View full text |Cite
|
Sign up to set email alerts
|

Four childhood atopic dermatitis subtypes identified from trajectory and severity of disease and internally validated in a large UK birth cohort

Abstract: Background Atopic dermatitis (AD) disease activity and severity is highly variable during childhood. Early attempts to identify subtypes based on disease trajectory have assessed AD presence over time without incorporating severity. Objectives To identify childhood AD subtypes from symptom severity and trajectories, and determine associations with genetic risk factors, comorbidities and demographic and environmental variables. Methods We split data from children in the Avon Longitudinal Study of Parents and Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Another study has incorporated eczema severity phenotypes while investigating eczema development up to age 14 years. 28 The participants of the Isle of Wight Birth Cohort (IOWBC) study have been seen on six occasions over the course of 26 years, at 1, 2, 4, 10, 18 and 26 years, with eczema being assessed at each follow-up. 29 Using data from the IOWBC, this study aims to investigate the natural course of eczema development from infancy to early adulthood in terms of identifying distinct developmental trajectories that describe disease patterns over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study has incorporated eczema severity phenotypes while investigating eczema development up to age 14 years. 28 The participants of the Isle of Wight Birth Cohort (IOWBC) study have been seen on six occasions over the course of 26 years, at 1, 2, 4, 10, 18 and 26 years, with eczema being assessed at each follow-up. 29 Using data from the IOWBC, this study aims to investigate the natural course of eczema development from infancy to early adulthood in terms of identifying distinct developmental trajectories that describe disease patterns over time.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have investigated eczema development up to 6 years, 25 10 years 27 and 16 years, 26 and hence, there is a need to investigate eczema trajectories beyond adolescence. Another study has incorporated eczema severity phenotypes while investigating eczema development up to age 14 years 28 …”
Section: Introductionmentioning
confidence: 99%
“…43,44 To date, longitudinal trajectories of AD have been mainly derived from questionnaire-based parental reports (summarized in Table S10; see Supporting Information). [13][14][15][16] In the comparable PRAD model, our study identified similar phenotypes, but the estimated prevalence of each phenotype differed from some previous studies. For example, the persistent phenotype was much more common in our study (12%) and in the Avon Longitudinal Study of Parents and Children (ALSPAC) (11%) 16 than in the Prevention and Incidence of Asthma and Mite Allergy (PIAMA) study (4Á9%) 14 and Generation R (2%).…”
Section: Discussionmentioning
confidence: 67%
“…Data‐driven techniques such as latent class analysis (LCA) have been used to disaggregate other atopic diseases, 12 and such an approach to derive longitudinal trajectories of AD may help in understanding its heterogeneity. To date, latent classes (often referred to as ‘phenotypes’) of childhood AD derived by LCA were reported in several birth cohorts 13–16 . Similar phenotypes have been identified across all studies, 13–15 including persistent, early‐onset and late‐onset AD 5,11 .…”
mentioning
confidence: 69%
“…In this issue of the BJD, Mulick et al 5 report on their study of 11 866 children from the Avon Longitudinal Study of Parents and Children birth cohort. The study aimed to classify AD into robustly identifiable subtypes, using data generated from questionnaires on the presence of flexural dermatitis and severity within the previous year, collected at 11 time points over the child's first 14 years of age.…”
mentioning
confidence: 99%